Assessment of the association between serum uric acid levels and the incidence of hypertension in nonmetabolic syndrome subjects: A prospective observational study - Chen, Qing; Yin, Yuan-Jun; Chen, Wei-Yan; Wu, Jian-Nong; Huang, Xuan (Medicine (Baltimore), 2018)
The purpose of this study was to examine the association between serum uric acid (sUA) and the incidence of hypertension in nonmetabolic syndrome (non-MetS) subjects.This was a prospective observational study including 23,525 subjects who had been followed up for at least 5 years. A logistic regression model was used to assess independent risk factors associated with hypertension. An area under the receiver operating characteristic curve (auROC) was generated, and a nomogram was developed to assess diagnostic ability of sUA and the sUA-based score.We enrolled 11,642 subjects, and 763 (6.55%) were diagnosed with hypertension at the 5-year follow-up. Subjects were classified into 4 groups based on the sUA quarter. Using Q1 as the reference group, Q2, Q3, and Q4 were found to show a higher risk for the development of hypertension with odds ratio of 1.51 (1.15, 1.98), 1.72 (1.30, 2.27), and 2.27 (1.68, 3.06), respectively (P < .001) after adjusting for other known confounding variables. Interaction analysis showed that there was no significant difference between subgroups stratified on the basis of sex, age, body mass index, fasting plasma glucose, and high-density lipoprotein cholesterol except triglycerides (P = .006). The auROCs for sUA and the sUA-based score were 0.627 (0.607, 0.647) and 0.760 (0.742, 0.777), respectively. A nomogram comprising independent risk factors was developed to predict the 5-year risk of hypertension for each subject.High sUA was significantly associated with the incidence of hypertension in non-MetS subjects adjusting for confounders.